2009
DOI: 10.1139/t08-102
|View full text |Cite
|
Sign up to set email alerts
|

A geophysical and geotechnical study to determine the hydrological regime of the Central Manitoba gold mine tailings deposit

Abstract: Extraction of gold from quartz–carbonate shear zones has left a barren deposit of tailings at Central Manitoba mine, which remains unchanged after 70 years. In this study, the shape of the basin, the groundwater and surface water flow regime, and the electrical conductivity of the tailings have been delineated using a combination of geotechnical, geophysical, and geochemical techniques. Groundwater and surface water flow from the north–south-fractured bedrock outwards to the east and west. A component of upwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The results (Fig. 4) showed that the enhanced conductivity occurs within the upper meter of the tailings and extends up to 0.5 m vertically (Sherriff et al, 2009). The zones of high conductivity are particularly prominent on steeply sloping areas at the southern side of the tailings pile.…”
Section: Central Manitoba Gold Mine Tailings Pilementioning
confidence: 91%
See 3 more Smart Citations
“…The results (Fig. 4) showed that the enhanced conductivity occurs within the upper meter of the tailings and extends up to 0.5 m vertically (Sherriff et al, 2009). The zones of high conductivity are particularly prominent on steeply sloping areas at the southern side of the tailings pile.…”
Section: Central Manitoba Gold Mine Tailings Pilementioning
confidence: 91%
“…Studies at this site (Davidson, 2005;Gupton, 2004;Gupton et al, 2004;Salzsauler, 2001;Sherriff et al, 2007Sherriff et al, , 2009) have provided constraints on the geological and geotechnical properties of the tailings and suggested its suitability for examining the ability of geophysical methods to map pH. Previous ground conductivity meter (EM38, EM31, and EM34) surveys at the tailings identified several areas of enhanced conductivity that were interpreted to correspond to zones of acid mine drainage (Sherriff et al, 2009). In the present study EM31 and DC-resistivity measurements were made along a carefully selected profile through a zone of enhanced conductivity.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…For the same purpose Lghoul et al applied a combination of ERT and seismic refraction tomography in Morocco [21], and HuotariHalkosaari and Lerssi [22] a combination of ERT and transient electromagnetic methods (TEM) in Finland. The electromagnetic methods capacitate fast geophysical reconnaissance of the polluted area [23]. Cabala et al [1] obtained promising results in distinguishing clear sands and two kinds of waste based on the results of EM measurements in the Olkusz region.…”
Section: Geoelectrical Surveymentioning
confidence: 99%